High temperature annealing of rare earth implanted GaN films: Structural and optical properties - Lorenz, K.
GaN epilayers grown by MOCVD were implanted with Tm and Eu under different implantation conditions, in order to optimize the implantation parameters of fluence, implantation temperature and energy. Rutherford backscattering spectrometry in the channelling mode (RBS/C), scanning electron microscopy (SEM), transmission electron microscopy (TEM), temperature-dependent photoluminescence (PL) and room temperature cathodoluminescence (CL) were used to study structural and optical properties of the samples. Different annealing methods are compared. According to RBS/C measurements, Tm at low fluences is found to incorporate entirely on substitutional Ga-sites while for higher fluences the substitutional fraction decreases. Increasing the fluence leads to increasing damage levels and finally to the formation of a partially amorphous, nanocrystalline surface layer. The luminescence intensity increases with fluence at first. However, for fluences in excess of 2 × 1015 Tm/cm2 it decreases again, showing a strong correlation between structural and optical properties. Implanting at higher temperature inhibits the formation of the nanocrystalline layer and increases both the substitutional fraction and the luminescence intensity. We also found that the presence of a thin AlN cap protects the sample during post-implant high temperature annealing and prevents the formation of a nanocrystalline surface layer during the implantation even for high fluences. The intensity of Eu-related CL near 622 nm at room temperature increases by a factor of 40 within the studied annealing range from 1000 to 1300 °C.